2023
DOI: 10.1371/journal.pone.0280375
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and its associated factors among under five years Muslim children of Kapilvastu district, Nepal

Abstract: Background Malnutrition is a major public health problem throughout the world especially in Southeast Asia. This study aims to find out nutritional status and its associated factors among under five Muslim children of Kapilvastu district Nepal. Methods Community based cross-sectional study was conducted among 336 under five Muslim children in Kapilvastu district Nepal from December 2021 to May 2022. Multistage probability random sampling was used. Among ten local units, three were selected randomly. Then fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
1
8
2
Order By: Relevance
“…Our findings showed that male children were more likely to be stunted than females. This is in line with studies conducted in Nepal 39 as well as various studies in Ethiopia and elsewhere, 40,41 which also have reported that under 5 male children are more likely to become stunted than their female counterparts. On the contrary, one of the studies conducted in South Asia found that female children were more likely to be stunted compared to males 42 .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings showed that male children were more likely to be stunted than females. This is in line with studies conducted in Nepal 39 as well as various studies in Ethiopia and elsewhere, 40,41 which also have reported that under 5 male children are more likely to become stunted than their female counterparts. On the contrary, one of the studies conducted in South Asia found that female children were more likely to be stunted compared to males 42 .…”
Section: Discussionsupporting
confidence: 91%
“…The association between parental education and nutritional status was only significant when assessed by MUAC, perhaps due to MUAC being a more sensitive indicator of wasting, especially in the setting of disease (47,48) . Parental education has been associated with wasting in other studies in Nepal and elsewhere (49,50) , as mothers who are less educated have been shown to have the poorest child feeding practices (4) . With this finding, focused interventions aimed at strengthening maternal education may be drawn.…”
Section: Discussionmentioning
confidence: 95%
“…These family and economic issues can significantly impact the nutritional status of school-age children. Previous studies have indicated that family size and the primary or formal caregiver are significant factors related to the nutritional status of school-age children [12,13]. The number of siblings was significantly related to nutritional status, with larger family sizes often leading to different nutritional outcomes [12].…”
Section: Introductionmentioning
confidence: 99%